Synthesis and Characterization of Phase Change Microcapsules Containing Nano-Graphite - Yeng-Fong Shih; Hong-Hao Chen (Advances in Technology Innovation, 2024)
This study uses the sol-gel method to modify the phase change microcapsules. The phase change material (PCM) is encapsulated by a polymer shell to reduce the leakage in the solid-liquid transition. Furthermore, the nano-graphite particle (NGP) is introduced into the shell to increase its thermal conductivity. The particle size and enthalpy value of the obtained microcapsules are approximately 3 μm and 150.3 J/g, respectively. The results show that the encapsulation efficiency of PCM in the prepared microcapsules is increased and the crystallization rate of PCM becomes faster when the NGP is added. The obtained microcapsules and wood flour are incorporated into high-density polyethylene (HDPE) to form a wood-plastic composite (WPC). The results indicate that the tensile and impact strengths of the WPC are 24.1 MPa and 48.7 J/m, respectively. Moreover, it is observed that the addition of these phase-change microcapsules can improve the heat dissipation of HDPE and accelerate the speed of thermal diffusion.